2017
DOI: 10.3390/polym9060236
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and Non-Isothermal Crystallization Studies of Long Chain Branched Polypropylene Containing Poly(ethylene-co-octene) under Quiescent and Shear Conditions

Abstract: Isothermal and non-isothermal crystallization behaviours of the blends of long chain branched polypropylene (LCB PP) and poly(ethylene-co-octene) (PEOc) with different weight ratios were studied under quiescent and shear flow using polarized optical microscopy (POM), differential scanning calorimetry (DSC), and rheological measurements. Experimental results showed that the crystallization of the LCB PP/PEOc blends were significantly accelerated due to the existence of the long chain branches (LCBs), the blends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Already crystallized inclusions of a dispersed polymer accelerate the crystallization of the matrix acting as nucleating agent and induce the formation of additional spherulites. Finally, the average spherulite radius in those blends becomes smaller than in plain iPP crystallized under the same condition [22]. Razavi-Nouri et al [23] studied the morphology of PP/linear low-density PE (LLDPE) blends and found that the nucleation densities of the PP spherulites decreased in the presence of the LLDPE.…”
Section: Introductionmentioning
confidence: 99%
“…Already crystallized inclusions of a dispersed polymer accelerate the crystallization of the matrix acting as nucleating agent and induce the formation of additional spherulites. Finally, the average spherulite radius in those blends becomes smaller than in plain iPP crystallized under the same condition [22]. Razavi-Nouri et al [23] studied the morphology of PP/linear low-density PE (LLDPE) blends and found that the nucleation densities of the PP spherulites decreased in the presence of the LLDPE.…”
Section: Introductionmentioning
confidence: 99%
“…This type of process offers very short reaction times, little or no use of solvents, simple product isolation steps, and relatively low infrastructure costs [11,12]. In the literature, PP-LCB is a well-studied topic with different approaches to improve the properties of linear PP and their disadvantages [13][14][15][16][17][18][19][20][21][22]. In addition to introducing LCB onto the backbone of PP, further competition reactions can take place.…”
mentioning
confidence: 99%
“…They further analyzed the effect of molecular weight of EOC on the crystallization rate of PP matrix in another piece of research 26 . The crystallization behavior of the PP/EOC blends was also studied by Zhang et al 27 They found that the crystallization of the blends was considerably enhanced due to the presence of the long‐chain branches and showed that the addition of EOC could also increase the crystallization rate of PP. Moreover, the results reported by Uthaipan et al 28 revealed that in comparison with the neat PP, the PP crystallization in the PP/EOC blends happened at a lower degree of undercooling with smaller crystal size and vulcanized EOC particles could accelerate the crystallization of the PP phase.…”
Section: Introductionmentioning
confidence: 99%